Experimental study on behaviour of segmental joints - Saibabu, S.; Jayaraman, R.; Lakshmanan, N.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Segmental concrete bridge construction describes a method of joining numerous cast-in-place or precast bridge elements to form a continuous span. This construction was first used in Europe in the 1950s and widely applied throughout world. It has many advantages over the conventional cast-in-place construction method. Segmental joints represent locations of discontinuity through which compression and shear forces are transmitted. The keys in the joints serve to transfer the shear force between segments during service. This paper presents the results of an experimental investigation that was performed at SERC, Chennai, to study the behaviour of the segmental joints at decompression, cracking and ultimate stages on a scaled model of a prototype girder. The behaviouir of the epoxy as a bonding material between the precast segments and shear force transfer was also studied. Design of the segmental girder, method of casting the segments and testing procedure are explained. The test specimen has an overall dimension of 5000mm length and 500mm depth. It consists of four numbers of each 750mm long mid-box segments and two numbers of each 1000mm long end segments. The segments were cast by using short line method and match casting. Epoxy mortar has been used to join the segments. External prestressing has been applied to assemble the segments. The test specimen was instrumented with LVDTs and dial gages. The specimen was subjected to two point loading and load increments of 22.5kN upto first cracking load. At each increment of load, all gauge responses were collected. Experimental results, deflection and stress increase in tendon are plotted against applied load. The results are compared with analytical computed values and found to be in good agreement.